TRANSFORMASI INDUSTRI MEDIA: ANALISIS STRUCTURE–CONDUCT–PERFORMANCE (SCP) PT SURYA CITRA MEDIA - Mahbub Ubaedi Alwi (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
The Indonesian media industry has undergone significant transformation driven by digitalization, market convergence, and regulatory change.These dynamics have reshaped market structure, corporate strategies, and economic performance, particularly among large media groups. This research investigates how these transformations occur by conducting a qualitative analysis based on the Structure–Conduct–Performance framework. It highlights PT Surya Citra Media Tbk as a case study representing leading media companies in Indonesia. The research uses a qualitative case study approach based on documents, utilizing annual reports, financial statements, and important policy documents from 2019 until the third quarter of 2025. Data are examined in an interpretive manner to track changes in ownership structure, strategic actions, and financial performance as time progresses. The results suggest that higher ownership concentration enhances strategic control and supports long-term investment decisions, especially in digital platforms and high-quality content. Corporate activity shows a gradual transition from depending on free-to-air television to a mixed business model that merges traditional broadcasting with digital services. Financial performance shows notable fluctuation, suggesting that short-term profitability pressures are closely linked to phases of investment and business model transformation rather than operational decline. This research illustrates that the Structure–Conduct–Performance paradigm continues to be relevant for examining modern media businesses, contingent upon a dynamic understanding of the interrelationships among its aspects. This study confirms the relevance of the Structure–Conduct–Performance framework for analyzing media industry transformation in the digital era, while contributing to media economics research and public understanding of the implications of ownership concentration and media transformation for industry governance and the information sphere.